Arms and munitions : circular / statement (1936)
015a_0029_001 ARMS AND MUNITIONS. There has been great concern in regard to the supplying of arms to the rebels by Germany and Italy. It is known that the rebels also have bought civil airplanes in this country. How far it will be possible for arms to be supplied by manufacturers in this country, probably through agents in another country, is a matter which has received attention, and on 10th August a circular was sent out to affiliated unions at the request of the I.F.T.U. urging members to keep particularly on the alert, in view of the fact that Fascist States and Parties would, at that time, do all they could, not only to give direct help to the rebels but also to order or obtain material of war indirectly from other countries and transport it across their countries. They were also asked, if their members were concerned with any phase of the manufacture or transport of munitions, to take such action as Executives considered necessary to secure and forward to us timely information of such orders or consignments as might be viewed with suspicion, having the above points in mind. 292/946/15a/29